Theory of Planetary Atmospheres : an Introduction to Their Physics and Chemistry. - Chamberlain, Joseph W. (Elsevier Science, 1989)
Our subject is, of course, nothing more than applied physics and chemistry. But in addition to those basic sciences the student of planetary atmospheres needs an overview of atmospheric structure and physical processes as presently understood. This book is intended to help fill that need for both graduate students and research scientists. Although the approach is mainly theoretical, very little basic physics is developed here. Material that is standard fare in third- and fourth-year physics courses is simply absorbed where needed.